One Year After Enrollment in Literacy Programs: A Study of Changes in Learners' Lives - Olga Ebert; Mary Beth Bingman (Adult Education Research Conference, 2000)
The study examined changes in the lives of 450 Tennessee adults one year after they enrolled in literacy programs. Among the findings were: increase in rate of employment, in participants’ self-esteem, in their involvement in community organizations, and in some literacy practices.